2018
DOI: 10.31788/rjc.2018.1143054
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Isotherm and Kinetic Studies Onto Removal of Reactive Yellow -14 Dye by Using Ixora Coccinea Leaf Powder

Abstract: Dyes are a complex organic compound which is used by various industries to color their products. These dyes enter the water which makes them polluted. Today, color removal from wastewater has been a matter of concern, both in the aesthetic sense and health point of view. Color removed from textile effluents on a continuous industrial scale has been given much attention in the last few years, not only because of its potential toxicity but also mainly due to its visibility problem. Ixora coccinea leaves have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The present study was carried out to evaluate the adsorption capacity of dye particles by using low cost PTLP.The study reveals that the parameters like sorption dose, contact time, pH have greater influence on the adsorption of RY-14 dye on PTLP. The optimum pH was found to be 2 for RY-14 dye 11 .Freundlich, Langmuir and Temkin isotherm models were studied and it concludes that Langmuir and Temkin suitably fits experimental data and Freundlich becomes inapplicable. Hence, it can be concluded that, PTLP be a better adsorbent for removing RY-14 from aqueous solutions.…”
Section: Resultsmentioning
confidence: 96%
“…The present study was carried out to evaluate the adsorption capacity of dye particles by using low cost PTLP.The study reveals that the parameters like sorption dose, contact time, pH have greater influence on the adsorption of RY-14 dye on PTLP. The optimum pH was found to be 2 for RY-14 dye 11 .Freundlich, Langmuir and Temkin isotherm models were studied and it concludes that Langmuir and Temkin suitably fits experimental data and Freundlich becomes inapplicable. Hence, it can be concluded that, PTLP be a better adsorbent for removing RY-14 from aqueous solutions.…”
Section: Resultsmentioning
confidence: 96%
“…Scanning Electron Microscopy studies were performed to characterize the surface morphology of the biomass before adsorption. considerable heterogeneous surface with a considerable number of cavities and more pores that can act as an excellent binding site for the dye adsorption 19 .…”
Section: Sem Analysismentioning
confidence: 99%
“…Applications of Reactive dyes around the globe are mostly used as cellulose fibers that possess main properties, such as having different brilliant shades of colors, soluble in water, affordable cost, the formation of a chemical covalent bond with the hydroxyl group of cellulose fibers, anionic and the color of the dyes shows fastness to washing 1 .Dyes are polymers, deeply colored and biodegradability is low in nature 2 . In spite of high solubility in water, that is well beyond to the naturally occurring chromophoric groups (like azo, oxazine group, anthraquinone, formazane, metallized azo and phthalocyanine) and the bridging groups (like ether or ester covalent chemical bond) linkages are present between dyes and fibers.…”
Section: Introductionmentioning
confidence: 99%
“…In 1916, Irving Langmuir proposed an adsorption model that explains the variation of adsorption capacity with pressure. This model is proposed by considering the uniform adsorptive surface of the adsorbent and adsorption with equal energies 26 . Langmuir isotherm describes the active surface area with a number of adsorption sites 9 .…”
Section: Langmuir Isothermmentioning
confidence: 99%